IMPLEMENTATION OF THE DUTIES OF THE VILLAGE HEADMAN IN VILLAGE DEVELOPMENT IN INDRAGIRI HILIR REGENCY BASED ON LAW NUMBER 6 OF 2014 CONCERNING VILLAGES - S Samsul Hadi; Sudi Fahmi; Ardiansah Ardiansah (JCH (Jurnal Cendekia Hukum), 2021)
Based on Article 26 paragraph (1) of Law Number 6 of 2014 concerning Villages it is stated that the village headman is in charge of administering village government, carrying out village development, developing village communities, and empowering village communities. The method used in this research is sociological law research. The implementation of the village headman's duties in village development in Indragiri Hilir Regency has not been carried out as regulated in Law Number 6 of 2014 concerning Villages. The obstacles in implementing the duties of the village head in village development in Indragiri Hilir Regency are the low quality of human resources of the village apparatus in Indragiri Hilir Regency, the lack of village offices and representative meeting rooms, village infrastructure in Indragiri Hilir Regency looks inadequate, and the lack of facilities and infrastructure in the form of computer technology that can be used to facilitate administrative services for the development of village development.